The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2298/avb0803179m
|View full text |Cite
|
Sign up to set email alerts
|

The influence of organic and inorganic Fe supplementation on red blood picture, immune response and quantity of iron in organs of broiler chickens

Abstract: The aim of this study was to investigate the influence of organic and inorganic Fe supplementation on red blood picture, immune response and quantity of iron in organs of broiler chickens. The trial was conducted on 200 'Arbor Acres' chickens randomly alloted in four equal groups. Birds from all groups were fed standard broiler feed, supplemented with 40 mg/kg of Fe originating from different sources: Group I (FeSO4), Group II (Fe bounded to yeast), Group III (ferrous ascorbate) and Group IV (iron chelate). Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nano-forms of Cu and Zn can have a cumulative influence and may become a substitute for chelated organic and inorganic forms and can improve animal performance and immunity ( 110 ). Svetlana et al ( 103 ) found that the degree of cutaneous hypersensitivity to phytohemagglutinin (PHA) at 21 and 35 days of age was greater in broilers given organic Fe, and Gumboro antibody titers at 35 days of age are increased in broilers offered iron chelator, but at 42 days of age, the differences are diminished among broilers.…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
See 1 more Smart Citation
“…Nano-forms of Cu and Zn can have a cumulative influence and may become a substitute for chelated organic and inorganic forms and can improve animal performance and immunity ( 110 ). Svetlana et al ( 103 ) found that the degree of cutaneous hypersensitivity to phytohemagglutinin (PHA) at 21 and 35 days of age was greater in broilers given organic Fe, and Gumboro antibody titers at 35 days of age are increased in broilers offered iron chelator, but at 42 days of age, the differences are diminished among broilers.…”
Section: Changes In Political and Social Conditions And Consumer Percmentioning
confidence: 99%
“…These benefits are critical for broilers and laying hens to prevent cage layer fatigue and poor eggshell quality (100)(101)(102). Essential micro-minerals such as zinc (Zn), iron (Fe), chromium (Cr), copper (Cu), selenium (Se) and iodine (I), are important as antioxidants and immune and health enhancers, and they are required for red blood cell and thyroid hormone functions (101)(102)(103)(104). In general, the recommended doses of trace minerals to boost immunity are ∼50-100% higher than the levels needed for productive performance.…”
Section: Mineralsmentioning
confidence: 99%